Causes of dust size variability in central East Antarctica (Dome B): Atmospheric transport from expanded South American sources during Marine Isotope Stage 2. (15th July 2017) - Delmonte, Barbara; Paleari, Chiara Ileana; Andò, Sergio; Garzanti, Eduardo; Andersson, Per Sune; Petit, Jean Robert; Crosta, Xavier; Narcisi, Biancamaria; Baroni, Carlo; Salvatore, Maria Cristina; Baccolo, Giovanni; Maggi, Valter
Abstract: We here investigate the spatial and temporal variability of eolian dust particle sorting recorded in the Dome B (77° 05′ S, 94° 55' E) ice core, central East Antarctica, during Marine Isotope Stage (MIS) 2. We address the question whether such changes reflect variable transport pathways from a unique source area or rather a variable apportionment from diverse Southern Hemisphere sources transported at different elevation in the troposphere. The Sr-Nd radiogenic isotope composition of glacial dust samples as well as single-particle Raman mineralogy support the hypothesis of a single dust provenance both for coarse and fine mode dust events at Dome B. The southern South American provenance of glacial dust in Antarctica deduced from these results indicate a dust composition coherent with a mixture of volcanic material and minerals derived from metamorphic and plutonic rocks. Additionally, Dome B glacial samples contain aragonite particles along with diatom valves of marine benthic/epiphytic species and freshwater species living today in the northern Antarctic Peninsula and southern South America. These data suggest contribution from the exposed Patagonian continental shelf and glacial outwash plains of southern Patagonia at the time when sea level reached its minimum. Our results confirm that dust sorting is controlled by the relative intensity of the two main patterns of tropospheric dust transport onto the inner Plateau, i.e. fast low-level advection and long-range high-altitude transport including air subsidence over Antarctica. Highlights: South American provenance of coarse- and fine-mode dust events at Dome B (Antarctica). Atmospheric circulation controls dust size variability in Antarctic ice cores. The Patagonian shelf became an important dust source during MIS 2 sea level minimum. Importance of Southern Patagonian glacial dust sources. Raman determination of micron-size mineral grains.